Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.0960-7412.2002.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for Arabidopsisβ1,2‐xylosyltransferase activity and targeting to the Golgi

Abstract: SummaryCharacterization of a b1,2-xylosyltransferase from Arabidopsis thaliana (AtXylT) was carried out by expression in Sf9 insect cells using a baculovirus vector system. Serial deletions at both the N-and C-terminal ends proved that integrity of a large domain located between amino acid 31 and the C-terminal lumenal region is required for AtXylT activity expression. The influence of N-glycosylation on AtXylT activity has been evaluated using either tunicamycin or mutagenesis of potential N-glycosylation sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
93
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 68 publications
13
93
1
Order By: Relevance
“…It was shown that the signal anchor sequence of a rat sialyl transferase (52 amino acids of the transmembrane domain and the cytoplasmic tail) and the equivalent sequence from a human galactosyl transferase was sufficient to target GFP to the Golgi stacks in tobacco leaf cells and BY2 suspension culture cells ( Boevink et al, 1998;Saint-Jore et al, 2002). Subsequently the equivalent sequences from recently cloned plant glycosyl transferases gave the same result ( Essl et al, 1999;Dirnberger et al, 2002;Pagny et al, 2003). These results suggest that the mechanisms of targeting and retention of glycosyl transferases may be conserved across kingdoms.…”
Section: Targeting Within the Golgisupporting
confidence: 57%
“…It was shown that the signal anchor sequence of a rat sialyl transferase (52 amino acids of the transmembrane domain and the cytoplasmic tail) and the equivalent sequence from a human galactosyl transferase was sufficient to target GFP to the Golgi stacks in tobacco leaf cells and BY2 suspension culture cells ( Boevink et al, 1998;Saint-Jore et al, 2002). Subsequently the equivalent sequences from recently cloned plant glycosyl transferases gave the same result ( Essl et al, 1999;Dirnberger et al, 2002;Pagny et al, 2003). These results suggest that the mechanisms of targeting and retention of glycosyl transferases may be conserved across kingdoms.…”
Section: Targeting Within the Golgisupporting
confidence: 57%
“…A putative type II xylosyltransferase is also predicted in the genome. This sequence shares 24% of identity with the luminal part of A. thaliana ␤(1,2)-xylosyltransferase involved in the transfer of a ␤(1,2)-xylose residue onto the ␤-Man of the N-glycan core (67,68). Nevertheless, in the absence of reported motifs specific for ␤(1,2)-xylosyltransferase activity, the involvement of this putative transferase in P. tricornutum N-glycan pathway remains highly hypothetical.…”
Section: Methodsmentioning
confidence: 97%
“…Using immunoelectronmicroscopic detection of a GFP that was N-terminally tagged with the 36 amino acid residues of the Arabidopsis XylT, the hybrid fluorescent protein has been shown to be concentrated mainly in the medial Golgi (17). Because our xylGalT comprises as much as 53 amino acids of the N terminus of the same xylosyltransferase (i.e., the region containing the cytoplasmic tail and the transmembrane domain), we suggest that this hybrid enzyme is also likely to be located in the medial Golgi.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies using hybrid glycosyltransferases have established that the cytoplasmic tail, transmembrane domains, and stem regions (i.e., the CTS domains) of several of these enzymes, including those of human GalT and plant core ␤-1,2-xylosyltransferase (XylT), play a decisive role in their sub-Golgi distribution (11,16,17). In the current study, we examined whether altering the localization of human GalT in plant cells by swapping its natural CTS domain with one from Arabidopsis thaliana XylT, could be used to modify N-glycosylation in plants and to reduce fucosylation and xylosylation of the chitobiose core.…”
mentioning
confidence: 99%